Lexical composition of effective L1 and L2 students' academic presentations. Issue 1 (13th September 2015) - Zareva, Alla
Abstract : The present study set out to examine the lexical profiles of L1 (n = 30) and proficient L2 students' presentations (n = 30), aiming at finding out the overall lexical composition of successful academic presentations. It was also of interest to see how some of the presentations' lexical features compared to findings about the lexical composition of students' productively used vocabulary in writing. In addition to this, the analysis focused on the lexical composition of both groups' oral production in an attempt to uncover patterns of lexical uses that may need to be discussed in oral communication courses, specifically targeting the development of L1 and L2 students' presentation skills. Overall, the analysis revealed more similarities than differences in the lexical composition of the L1 and L2 presentations while, at the same time, outlined few areas that need to be addressed in oral academic instruction.